Fine sediment loads and dynamics in Baleh River, Sarawak - Janggu, Joyce Anak (2024)
Dams are well known to cause changes in sediment dynamics in downstream rivers, as a result of sediment trapping by the dam and changes in flow competence. While a major programme of dam building is underway in the tropics, the vast majority of fluvial geomorphic studies of dams globally have taken place in temperate and Mediterranean climate regions. More generally, sediment loads in tropical system are less well known than those in more northerly regions. Hence, there are fundamental and applied knowledge gaps related to fluvial processes in tropical rivers.